Hydrocortisone treatment is associated with early recovery from severe septic shock in patients with obstructive pyelonephritis due to upper urinary tract stone - Isamu Otsuka; Koshiro Nishimoto; Taichi Kozako; Katsuhiro Kanemaru; Yasuhiro Yamashita; Toshiyuki Kamoto; Atsuro Sawada (BJUI Compass)
Abstract Objectives The administration of hydrocortisone in patients with severe septic shock contributes to early recovery in intensive care. The purpose of this study was to evaluate the effect of hydrocortisone on early recovery from severe septic shock in patients with obstructive pyelonephritis due to upper urinary tract stone (stone pyelonephritis). Methods From January 2018 to October 2023, of all patients admitted for treatment of stone pyelonephritis, 28 did not respond to initial fluid infusion and vasopressors for urosepsis. Among these 28 patients, 14 were administered hydrocortisone for recovery from early shock. Characteristics and noradrenaline administration time of patients treated or not treated with hydrocortisone were retrospectively analysed. Results In patients with septic shock associated with stone pyelonephritis unresponsive to initial fluid and vasopressors, noradrenaline administration time in the hydrocortisone group (28.7 ± 17.5 h) was significantly shorter than in the non‐treated group (46.0 ± 12.8 h, p = 0.006). The factors diabetes, blood culture results, age, performance status, severity of vital signs and laboratory data on sepsis severity were not significantly associated with the duration of noradrenaline administration. Conclusions Our findings suggest potential benefits of hydrocortisone administration for stone pyelonephritis unresponsive to initial fluid and vasopressors. Widespread adoption of hydrocortisone in the treatment of sepsis, which is common in intensive care, could become more important in urology.